Strategi Pengembangan Even Di Museum Untuk Meningkatankan Kunjungan Wisatawan Ke Museum R.A Kartini Rembang - Muhammad Nilzam Aly (Media Wisata, 2018)
This research discusses the development strategy undertaken by the manager of R.A Kartini Museum especially related to the implementation of an event held in R.A Kartini Museum, Rembang Regency. This research is a qualitative descriptive research supported by the use of quantitative data such as the number of tourist visits. The results of research advised that the R.A Kartini Museum manager must consider the expectations and necessary of the visitors with the main purpose of the museum. The educational missions need more attention by the manager of R.A Kartini Museum one of them with the implementation of the event. So hope the museum is not like a storehouse of historical objects but can also be a media trip and have fun that reaches all levels of society